Dampak Inovasi Produk Dan Penggunaan Media Sosial Terhadap Keputusan Pembelian Studi Kasus Pada Produk Kemplang Panggang Palembang Amanda - Fuadi, Selamet; Fitriani, Fitriani; Ramalia, Desi (Universitas Muhammadiyah Metro, 2023)
Entrepreneurial competition is currently very high because all companies are constantlytrying to increase their market share by getting new customers. Business conditions changedynamically with changes in the surrounding environment and changes in the tastes ofconsumers who are increasingly diverse. The community is required to be creative byprocessing fish into other processed fish products such as kemplang biscuits, these processedproducts are very popular with the community for complementary foods. This study aims todetermine 1) To find out whether product innovation has an effect on purchasing decisions.2) To find out whether the use of social media has an effect on purchasing decisions. 3) Tofind out the variables of product innovation and the use of social media together have aneffect on purchasing decisions. This study uses a quantitative approach. The survey methodwas chosen as the primary data source. The survey method focuses on collecting data fromrespondents who have certain information, thus enabling researchers to solve problems. Inthis study, the population was taken based on consumers who made purchases of AmandaKemplang crackers as many as 115 per month. Data collection techniques using aquestionnaire with a Likert scale. The results showed that 1) there was a positive and significant influence between product innovation on purchasing decisions. 2) there is apositive and significant influence between social media on purchasing decisions. 3) there is apositive and significant influence between product innovation and the use of social mediatogether on purchasing decisions